Organizational Design and Rules in Rastin Profit and Loss Sharing Banking - Bidabad, Bijan; Mohammadi, Roohollah; Sherafati, Mahshid (International Journal of Small and Medium Enterprises, 2019)
Purpose: This paper aims to explain the organizational structure of Rastin Profit and Loss Sharing (PLS) Banking. Rastin Banking is a full Islamic Banking System with all necessary parts for banking operations that can be installed in conventional and Islamic banks both. Design: Rastin Banking complies with the nature of the financial intermediary activity (the partnership of depositor in the yields of the fund receiver via the bank). To fulfill this goal, particular organizational structure, accompanying with instruments and workflow are defined. Findings: To handle Rastin Banking, particular theoretical and operational regulatory frameworks should be defined to fulfill the participation operations. In this paper, we will have a look at the necessary organizational structure to setup Rastin Banking. Research limitations: This plan was formed and tested in Bank Melli Iran in order to propose a model for other banks as well. Practical implications: In this system, the investment return of the participation is distributed to the parties of the financial partnership (depositor, entrepreneur, and bank), and it is done by eliminating fixed interest rate, and it is based on the real economy profit (return) of the activity. Social implications: Rastin Banking can lead to important positive effects on growth and economic welfare through money and capital markets. Interest rate as an essential factor in conventional banking is not usable in Islamic banking and other similar institutions that work based on partnership, such as mutual funds and saving and loan associations. Originality/value: Approach of this system is entirely different from conventional banking. In addition to removing usury in banking activities, Rastin Banking uses the best practical ethic finance to creating safe and public confidence environment for banking operations. Article Type: Technical paper